Сравнение характеристик асинхронного двигателя с короткозамкнутым ротором при замене материала обмотки ротора и предложения по их улучшению - Шевченко, Валентина Владимировна; Горюшкин, Никита Игоревич; Лизан, Игорь Ярославович (НТУ "ХПИ", 2014)
В статье проанализированы вопросы изменения геометрии зубцовой зоны ротора асинхронного двигателя, которые необходимо выполнить при изменении материала обмотки ротора, с целью обеспечения достаточных пусковых характеристик и сохранения энергетических показателей.

Have been analyzes the questions of the changes the geometry toothed zone asynchronous motor rotor, that must be done when changing the material of the rotor winding. It is noted that the use of the asynchronous generator with wound cast copper rotor winding instead of cast aluminum winding, is not a problem. But for motors with rotor copper windings should conduct additional studies to ensure acceptable starting characteristics and conservation of energy indicators. It was found that the deepening of rotor slot by 15 % will lead to increased influence of crowding out current and will provide for the asynchronous motor with a copper rotor winding same starting characteristics, which have been the engine with aluminum one. The results were obtained under the condition of conservation cross-sectional area of the groove, i.e. copper consumption and cost.
A comparison of the asynchronous motor characteristics with squirrel cage by replacing the material of the rotor winding and suggestions for improvement
Keywords: форма паза ротора; медная обмотка; алюминиевая обмотка; энергетические показатели; asynchronous motor; rotor; shape groove of the rotor winding; copper winding; aluminum winding